The Survey of the Health of Wisconsin (SHOW) Program: An Infrastructure for Advancing Population Health - Malecki, Kristen M. C.; Nikodemova, Maria; Schultz, Amy A.; LeCaire, Tamara J.; Bersch, Andrew J.; Cadmus-Bertram, Lisa; Engelman, Corinne D.; Hagen, Erika; McCulley, Laura; Palta, Mari; Rodriguez, Allison; Sethi, Ajay K.; et al. (Frontiers in Public Health, 2022)
Introduction The Survey of the Health of Wisconsin (SHOW) was established in 2008 by the University of Wisconsin (UW) School of Medicine and Public Health (SMPH) with the goals of (1) providing a timely and accurate picture of the health of the state residents; and (2) serving as an agile resource infrastructure for ancillary studies. Today, the SHOW program continues to serve as a unique and vital population health research infrastructure for advancing public health. Methods SHOW currently includes 5,846 adult and 980 minor participants recruited between 2008 and 2019 in four primary waves. WAVE I (2008–2013) includes annual statewide representative samples of 3,380 adults ages 21 to 74 years. WAVE II (2014–2016) is a triannual statewide sample of 1,957 adults (age ≥18 years) and 645 children (age 0–17). WAVE III (2017) consists of follow-up of 725 adults from the WAVE I and baseline surveys of 222 children in selected households. WAVEs II and III include stool samples collected as part of an ancillary study in a subset of 784 individuals. WAVE IV consists of 517 adults and 113 children recruited from traditionally under-represented populations in biomedical research including African Americans and Hispanics in Milwaukee, Wisconsin. Findings to Date The SHOW resource provides unique spatially granular and timely data to examine the intersectionality of multiple social determinants and population health. SHOW includes a large biorepository and extensive health data collected in a geographically diverse urban and rural population. Over 60 studies have been published covering a broad range of topics including, urban and rural disparities in cardio-metabolic disease and cancer, objective physical activity, sleep, green-space and mental health, transcriptomics, the gut microbiome, antibiotic resistance, air pollution, concentrated animal feeding operations and heavy metal exposures. Discussion The SHOW cohort and resource is available for continued follow-up and ancillary studies including longitudinal public health monitoring, translational biomedical research, environmental health, aging, microbiome and COVID-19 research.